2014
DOI: 10.1016/j.jiph.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Culminating anti-malaria efforts at long lasting insecticidal net?

Abstract: Specific criteria for determining the serviceable life and guidelines on the safe washing and disposal of LLINs need to be developed, kept well-informed and closely monitored. Malaria case management, environment management and community awareness to reduce the misuse of LLINs are crucial. Focused research on developing effective anti-malarial drugs, vaccines and new insecticides to reduce resistance is imperative to tackle malaria in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Lack of awareness could also lead to serious consequences that may thwart control programmes. A recent review [69] has highlighted that ITNs distributed free of cost to the people living in endemic areas may not be used for the purpose they are meant for, but used for catching fishes in the streams and rivers and to store food material. ITNs and LLINs users are sufficiently educated about the benefits of nets while used for personal protection and also about the disadvantages when misused for deviant reasons.…”
Section: Challenges In Achieving Malaria Eliminationmentioning
confidence: 99%
“…Lack of awareness could also lead to serious consequences that may thwart control programmes. A recent review [69] has highlighted that ITNs distributed free of cost to the people living in endemic areas may not be used for the purpose they are meant for, but used for catching fishes in the streams and rivers and to store food material. ITNs and LLINs users are sufficiently educated about the benefits of nets while used for personal protection and also about the disadvantages when misused for deviant reasons.…”
Section: Challenges In Achieving Malaria Eliminationmentioning
confidence: 99%
“…Synthetic pyrethroids including deltamethrin and lambda-cyhalothrin are widely used in various public health programmes to control mosquitoes in many countries. However, in the recent years efficacy of these insecticides against potential malaria vectors has been found to reduced in endemic areas [ 2 , 3 , 6 , 17 , 34 ]. The present study area has vast paddy fields and large scale vegetable cultivation throughout the year, and the pyrethroids are widely used in the control of agricultural pests.…”
Section: Discussionmentioning
confidence: 99%
“…These areas are exposed to intense and constant malaria transmission all year round; hence, the population living for a long time tends to develop high levels of immunity against malaria ( 14 ). In endemic areas, progressive acquisition of immunity with age is observed, which results in decreased malaria incidence with increasing age ( 15 , 16 ). Studies have suggested that the time to acquire clinical immunity against malaria depends on the intensity of transmission, interventions used, and genetic diversity of malaria parasite ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%